The Influence Concerning Social Media and Religious Values Concerning The Boycott of Pro-Israel Products in Medan City - Rahma, Nopita; Albani Nasution, Muhammad Syukri; Harahap, Muhammad Ikhsan (Universitas Ibn Khladun Bogor, 2025)
The action of rejecting pro-Israel local goods in Indonesia has intensified in response to the ongoing Palestine–Israel conflict, with social media playing a pivotal role in mobilizing public sentiment. This study investigates the role of social media and religiosity on boycott behavior in the city of Medan. Employing a a quantitative technique through multiple linear regression analysis, data were gathered from 100 respondents who are active social media users and knowledgeable about the Palestinian issue. The results indicate that social media significantly influences boycott behavior (p = 0.044), while religiosity exerts an even stronger and highly significant effect (p = 0.001). Together, These elements explain 69.6% of the differences in boycott actions.The findings highlight that boycott behavior is not merely driven by emotions but is shaped by both digital information dissemination and deep-rooted religious values.